Skin colour is associated with periodontal disease in Brazilian adults: a population-based oral health survey - Marco Aure´ lio Peres (Blackwell Synergy, 2007)
Aim: To estimate the prevalence of periodontal disease in Brazilian adults and to test its association with skin colour after controlling for socio-demographic variables. Methods: The periodontal status of 11,342 Brazilian adults was informed by a nationwide oral health survey. Socio-demographic variables included skin colour, gender, schooling, per capita income, age and geographical region. The association between periodontal disease and skin colour was tested by a logistic regression model, adjusting for covariates. Interactions between skin colour and socio-demographic variables were tested. Results: The prevalence of periodontal diseases was 9.0% [95% confidence interval (CI) 7.6–10.3]. Lighter-skinned black people (pardos) and dark-skinned black people (pretos) presented higher levels of periodontal disease when compared with white people [odds ratio (OR)51.5; 95% CI 1.2; 1.8; OR51.6; 95% CI 1.2; 2.1, respectively] even after controlling for age, gender, schooling, per capita income and geographic region. No interactions were statistically significant. Conclusion: Skin colour was significantly associated with periodontal disease among Brazilian adults after adjustment for socio-economic and demographic covariates.